Association of B7H3 with HIF-1α nuclear expression indicates poor prognosis and therapeutic potential in gastric cancer - Li, Mengsi; Guo, Tianwei; Wang, Ziyi; Liu, Xue; Guo, Lingchuan; Cao, Lei (Frontiers in Oncology, 2026)
B7H3 (B7 homolog 3) is an important immune checkpoint molecule in the B7-CD28 family, and substantial evidence indicates that it promotes tumor growth, invasion, and metastasis. The imbalance between oxygen supply and consumption in the tumor microenvironment induces hypoxia, which activates hypoxia-inducible factor-1α (HIF-1α) signaling. HIF-1α plays a critical role in tumor growth, metastasis, and immune evasion. However, the interaction between HIF-1α and B7H3 in gastric cancer remains unclear. In this study, we explored the expression characteristics and correlation of B7H3 and HIF-1α in large gastric cancer samples using bioinformatics and immunohistochemical methods. The results show that B7H3 and HIF-1α mRNA are significantly upregulated in gastric cancer, with a strong positive correlation between their expressions. In gastric cancer tissues, no significant correlation was found between B7H3 and HIF-1α expression (rS = 0.070, P = 0.257), whereas high B7H3 expression demonstrated a moderate positive correlation with nuclear expression of HIF-1α (rS = 0.141, P = 0.021). Furthermore, we found that nuclear expression of HIF-1α was closely associated with poor prognosis in gastric cancer patients (P < 0.001) and could serve as an independent risk factor. Notably, knockdown of B7H3 in gastric cancer cells significantly inhibited both the expression and nuclear localization of HIF-1α, whereas overexpression of B7H3 markedly promoted HIF-1α expression. In conclusion, the combination of B7H3 and HIF-1α may serve as a novel prognostic biomarker for gastric cancer and also holds potential as a therapeutic target for its treatment.